Novel of Tuberculosis Vaccine Candidates through In Silico and In Vivo Analysis of Single Epitope Protein PE-PGRS Mycobacterium Tuberculosis - Adha, Muhammad Alghifary; Maulana, Rafi; Mifindra, Rafhy (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Tuberculosis (TB) is an infectious disease that remains a serious global health threat. The use of the Bacille Calmette–Guérin (BCG) TB vaccine has so far shown unsatisfactory results due to its inconsistent and limited effectiveness. In this study, a comprehensive preclinical study pipeline was developed to design a novel single-epitope subunit vaccine targeting the PE_PGRS protein family of Mycobacterium tuberculosis. VaxiJen screened antigenic proteins, IEDB and NetMHCpan predicted B- and T-cell epitopes. Selected epitopes were assembled with linkers and an adjuvant. The construct was expressed, purified, and tested in vivo in mice for antibody and cytokine responses. The construct result showed, which had a molecular weight of 35.1 kDa and an instability score of 16.58, was found to be stable, soluble, and somewhat hydrophilic by physicochemical examination. The three-dimensional model showed a tight and stable fold that was dominated by ?-sheets and ?-helices. Strong binding affinities with MHC class I (?G = ?22.7 kcal/mol) and class II (?G = ?10.9 kcal/mol) were confirmed by molecular docking and PRODIGY studies. In the in vivo test, the single epitope exposure group had an average value of 0.090 ± 0.017. This indicates that single epitope exposure provides a significant effective antigen presentation and T-cell activation and increase in the measured parameters compared to the control group. Collectively, these findings highlight the potential of the designed single-epitope construct as a safe, stable, and immunogenic vaccine candidate against M. tuberculosis, meriting further experimental validation.